The Hubungan Aktivitas Fisik dan Keseimbangan Dinamis terhadap Kualitas Hidup Pada Lansia - Nadhia Febriana; Abdul Chalik Meidian; Nuraini Diah Novianti; Muthiah Munawarah; Jerry Maratis (LPPM Universitas Abdurrab, 2026)
Abstract Objective: This study to determine the relationship between physical activity and dynamic balance on quality of life in the elderly. Methods: This type of research is a descriptive correlative study between physical activity and dynamic balance on quality of life in the elderly at the Panti Werdha Wisma Mulia, West Jakarta with purposive sampling data collection technique. Physical activity examination using the Physical Activity Scale for Elderly (PASE) questionnaire, dynamic balance measurement using the 10 Step Tandem Test measuring instrument, and quality of life examination using the World Health Organization Quality of Life-BREF (WHOQOL-BREF) questionnaire. Results: The Mean±SD value of physical activity was 13.62±3.373 and the Mean±SD value of dynamic balance was 3.24±0.802, and the Mean±SD value of quality of life was 82.47±9.109. Then, the results of the hypothesis test using the Spearman Rank Test on the physical activity variable obtained a p value = 0.007 where p <α value (0.05) and r value = 0.397 which means there is a significant relationship between physical activity and quality of life in the elderly. While on the dynamic balance variable obtained a p value = 0.184 where p> α value (0.05) and r value = 0.202 which means there is no significant relationship between dynamic balance and quality of life in the elderly. Conclusion: there is a significant relationship between physical activity and quality of life in the elderly and there is no significant relationship between dynamic balance and quality of life in the elderly.